Analysis of Growth, Recruitment Patterns, Mortality, and Exploitation Rate of Yellowfin Tuna (Thunnus albacares) Landed at Kendari Ocean Fishing Port (PPS) - Nawir, Muh. Fahmi Saputra; Asriyana, Asriyana; Nur, Andi Irwan (Jurnal Biologi Tropis, 2025)
Population parameters such as growth, recruitment patterns, mortality, and exploitation rates have a very crucial role in sustainable fisheries resource management. This study aims to analyze the growth, recruitment patterns, mortality, and exploitation rate of yellowfin tuna (Thunnus albacares) at the Kendari Ocean Fishing Port. Data were obtained from fishermen's catches using mini purse seine fishing gear at the Kendari Ocean Fishing Port (PPS) during the period June to November 2024. The analysis was carried out using the von Bertalanffy method for growth, recruitment patterns, mortality estimation, and exploitation using FiSAT II software. The findings indicated that the yellowfin tuna's estimated maximum length (L∞) reached 70.20 cm, with an annual growth coefficient (K) of 0.50. The recruitment trend revealed a significant peak in August, registering a rate of 19.55%. The total annual mortality rate (Z) was noted at 6.14, comprising a natural mortality (M) rate of 0.90 per year and a fishing mortality (F) rate of 5.25 per year. The exploitation rate (E) calculated at 0.85 per year suggests that the yellowfin tuna caught at Kendari PPS in the Banda Sea is subject to overfishing. This analysis offers crucial insights for the sustainable management of yellowfin tuna stocks and suggests that additional research on the fishing equipment employed in the Banda Sea for capturing yellowfin tuna be conducted.